The risk of smoking with stroke in Asia : meta-analysis - Fadhilatul Hasnah; Yuniar Lestari; Abdiana Abdiana (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
This study uses a systematic method of review and meta-analysis to look at the risk of smoking with stroke in Asia. Further analysis based on the stroke subtype (ischemic stroke and haemorrhagic stroke was also carried out. Literature search was carried out in the PubMed, EBSCO and Google Scholar databases. Q tests were performed to determine the heterogeneity of included studies. Funnel plot, Egger regression test and trim and fill methods were used to identified publication bias and with the transformation of the model between the fixed effect model and the random effect model for sensitivity analysis A total of 12 articles were included consisting of 9 studies with case control design studies and 3 studies with cohort designs. The meta-analysis results showed that people who smoke have risks pooled OR 2.04 times (95% CI 1.57-2.65) for having a stroke Analysis of the type of stroke, smokers had 2.3 times the risk of having an ischemic stroke or 2.77 times for having a haemorrhagic stroke. Eggers test showed no influence of publication bias on the meta-analysis of smoking with stroke to. From this meta-analysis, it can be concluded that smoking increasing risk for stroke. This study found the risk of smokers to have a haemorrhagic stroke is higher than ischemic stroke.